(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
Extant anoxic basins in the Eastern Mediterranean have been continuously studied with multidisciplinary approach since 1983, year of their discovery. They form after dissolution of Messinian evaporites on the flank of deep-sea rimmed depressions. Anoxia is due to brine density stratification which prevents bottom water ventilation. The state of the art of the geological and geochemical knowledge is presented and the need for further investigation is stressed.